Rancang Bangun Aplikasi Pendeteksi Tingkat Kepekatan Asap Hasil Pembakaran Berbasis Internet of Things - Somantri, S; Kharisma, Ivana Lucia; Angelina, Nadila (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The objective of this study is to develop and construct an Internet of Things (IoT) system(Internet of Things) application for detecting the concentration level of smoke resulting from combustion. The current advancement in technology has had a significant Significant influence across a range of domains, encompassing the realm of Internet of Things (IoT). The IoT network allows devices to interact and exchange information automatically, enhancing efficiency and security in various sectors. Early detection of smoke is crucial for preventing further damage and protecting human health. Therefore, this research utilizes MQ-135 and TGS 2600 sensors as smoke detection sensors. Through IoT, real-time measurement of smoke concentration can be achieved, enabling immediate actions in response to significant changes. The data collected through IoT can to enhance effectiveness, the information can be stored within a database and efficient research. By implementing this application, it is expected to provide a better solution for automatic detection and monitoring of smoke resulting from combustion, reducing air pollution risks, and enhancing human safety.